BAT-Net: An enhanced RNA Secondary Structure prediction via bidirectional GRU-based network with attention mechanism. (December 2022) - Shen, Cong; Chen, Yu; Xiao, Feng; Yang, Tian; Wang, Xinyue; Chen, Shengyong; Tang, Jijun; Liao, Zhijun
Abstract: Background: RNA Secondary Structure (RSS) has drawn growing concern, both for their pivotal roles in RNA tertiary structures prediction and critical effect in penetrating the mechanism of functional non-coding RNA. Computational techniques that can reduce the in vitro and in vivo experimental costs have become popular in RSS prediction. However, as an NP-hard problem, there is room for improvement that the validity of the prediction RSS with pseudoknots in traditional machine learning predictors. Results: In this essay, by integrating the bidirectional GRU (Gated Recurrent Unit) with the attention, we propose a multilayered neural network called BAT-Net to predict RSS. Different from the state-of-the-art works, BAT-Net can not only make full use of the information about the direct predecessor and direct successor of the predicted base in the RNA sequence but also dynamically adjust the corresponding loss function. The experimental results on five representative datasets extracted from the RNA STRAND database show that the sensitivity, precision, accuracy, and MCC (Matthews Correlation Coefficient) of the BAT-Net have improved by 8.52%, 8.28%, 5.66% and 9.82%, respectively, compared with the benchmark approaches on the best averages. Conclusions: BAT-Net can provide users with more credible RSS results since it has further utilized the source information of the dataset. Comparative results show that the proposed BAT-Net is superior to the other existing methods on the relevant indicators. Graphical abstract: Highlights: An enhanced RNA secondary structure prediction is proposed in this article. It can make full use of both the direct predecessor and successor information. The algorithm framework can dynamically adjust the corresponding loss function. Results show that the proposed strategy is superior to the other existing methods.